Analysis of Factors Influencing User Satisfaction with The Benefits of The Information System In The SIPD-SIKD Application of The Special Capital Region of Jakarta - Khairunnisa, Peni; S. Setyowati, Milla (Asian Journal of Social and Humanities, 2024)
The use of the Regional Government Information System (SIPD) is increasingly important to optimize the performance of local governments, one of which is in regional financial management which is carried out electronically with the implementation of the Regional Financial Information System (SIKD). The success of the implementation of SIPD-SIKD does not only depend on the technical aspect, but also on the level of acceptance and user satisfaction with the benefits of the information system, as measured by the level of user satisfaction and the intensity of using the system. This study aims to analyze the factors that affect user satisfaction with the benefits of information systems. This study integrates the UTAUT and Delone-McLean models, both models describe the relationship between variables and take into account user behavior when using information systems, as well as measure the success of information systems through user satisfaction. This study uses a quantitative approach with data collection techniques using questionnaires distributed online as many as 350 respondents. The analysis technique in this study uses SEM-PLS using SmartPLS software. Based on the results of data processing, it shows that performance expectations, business expectations, facilitation conditions, information quality, and system quality have an influence on user satisfaction. Furthermore, user satisfaction affects the benefits of information systems both at the individual and organizational levels.